Assessing seizure liability in vitro with voltage-sensitive dye imaging in mouse hippocampal slices - Utsumi, Yuichi; Taketoshi, Makiko; Miwa, Michiko; Tominaga, Yoko; Tominaga, Takashi (Frontiers in Cellular Neuroscience, 2023)
Non-clinical toxicology is a major cause of drug candidate attrition during development. In particular, drug-induced seizures are the most common finding in central nervous system (CNS) toxicity. Current safety pharmacology tests for assessing CNS functions are often inadequate in detecting seizure-inducing compounds early in drug development, leading to significant delays. This paper presents an in vitro seizure liability assay using voltage-sensitive dye (VSD) imaging techniques in hippocampal brain slices, offering a powerful alternative to traditional electrophysiological methods. Hippocampal slices were isolated from mice, and VSD optical responses evoked by stimulating the Schaffer collateral pathway were recorded and analyzed in the stratum radiatum (SR) and stratum pyramidale (SP). VSDs allow for the comprehensive visualization of neuronal action potentials and postsynaptic potentials on a millisecond timescale. By employing this approach, we investigated the in vitro drug-induced seizure liability of representative pro-convulsant compounds. Picrotoxin (PiTX; 1–100 μM), gabazine (GZ; 0.1–10 μM), and 4-aminopyridine (4AP; 10–100 μM) exhibited seizure-like responses in the hippocampus, but pilocarpine hydrochloride (Pilo; 10–100 μM) did not. Our findings demonstrate the potential of VSD-based assays in identifying seizurogenic compounds during early drug discovery, thereby reducing delays in drug development and providing insights into the mechanisms underlying seizure induction and the associated risks of pro-convulsant compounds.